REPRODUCTIVE CONSTRAINTS IN THE RUSSIAN INDUSTRIAL DEVELOPMENT - Rodion R. Tokov; Violetta V. Rokotyanskaya (Статистика и экономика)
The article examines the main factors restraining the activity of industrial development at the present stage of Russian reforms. Special attention is paid to innovation activity of organizations, industries, business confidence, high level of taxation, the lack of funds and lack of demand on the domestic market.